Effect of daylight saving time on Bangladesh power systems - Sarwar, Rashed; Ahmed, Khaza Moin-uddin; Chakrabartty, Rajib; Ahmed, Nisa (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.